Role of physical activity in GLP-1 receptor agonist therapy for obesity treatment - Łukasz Zdziebkowski; Hanna Wilska; Dorota Szatkowska; Dominika Ziętara; Kacper Kmieć; Aleksandra Topolska; Marcin Komorowski; Michał Janiszewski; Natalia Surosz; Michał Grochowalski; Aleksandra Graczyk; Jakub Szydło (Quality in Sport, 2025)
Introduction: WHO recognized it as a global obesity crisis. Globally there are 2,5 billion adult people living with excess body weight (43% of global adult population). Out of these 890 million have obesity disease (16% of global adult population). This forces to implement safe and effective body mass reduction treatment.